The influence of the CommonLit platform on the development of reading skills as an academic reinforcement for A2 students - Buñay Illapa, Elsy; Bajaña Rosales, Mónica Elizabeth; Campoverde López, Johnny Segundo; Bonilla Tenesaca, Josué (Arandu UTIC, 2024)
Ecuador, a country of privileges due to its geographical location, has varied socio-ideological and cultural influences that significantly impact the learning and acquisition of a foreign language. Few students are aware of the importance of English. However, many do not feel a real interest in or the need to use the language in their daily activities in a society where they only try to cover a momentary requirement. The complexity of mastering a new language like English is even worse because learners have to face environmental, and emotional difficulties, as reflected in the quantitative study carried out, which suggests energizing their learning acquisition using the qualitative method that promotes their voluntary interest in reading comprehension, as stated by a survey and class observation carried out in the First “A” of Accountancy at the Isabel de Godin Educative Unit in Riobamba. Therefore, the implementation of the CommonLit platform will determine academic progress and reading proficiency as the main tool to improve their reading skills by addressing challenges according to different levels of English proficiency. In this sense, with the platform's interactive activities, adaptive learning tools, and variety of interesting information, participants' reading abilities significantly improve, according to the findings. Therefore, the CommonLit platform is a useful tool for students who intend to achieve A2 in their reading development since it enhances the academic level and cultivates an enduring enjoyment for reading.